Intimate Partner Violence and its Associated Factors Against Currently Married Women in Nepal (Journal of Population and Development, 2023)
Intimate partner violence (IPV) is a major public health and human rights issue in Nepal. This paper aims to assess factors associated with intimate partner violence against currently married women in Nepal. Data for this study is derived from the Nepal Demographic Health Surveys (NDHS) of 2022. A sample of 3,839 currently married women of reproductive age (15-49 years) who participated in the domestic violence module of the survey are included Physical, emotional, and sexual violence against women by husbands is considered as dependent variables. Any type of violence is derived from these three types of violence. The chi-square test is used to test the significant association between two variables. Logistic regression was used to assess the net effect of several independent variables, the result revealed that more than one-fourth (27%) of currently married women experienced any form of IPV with more than one-fifth (23.1%) physical, approximately one-eighth (12.8%) sexual, and less than one-tenth (7.1%) emotional violence. In multivariate logistic regression analysis, age at first marriage, women’s education, ethnicity, ecological zone, wealth index, husband education, and husband’s alcohol consumption are highly significant associations with intimate partner violence, as indicated by the very low p-values (